Pain tolerance in upper limb disorders: findings from a community survey. Issue 3 (1st March 2003) - Mitchell, S; Reading, I; Walker-Bone, K; Palmer, K; Cooper, C; Coggon, D
Abstract : Aims: To test the hypothesis that non-specific upper limb pain arises from altered pain perception with reduced tolerance of sensory stimuli. Methods: Subjects undergoing clinical examination as part of a community based survey of upper limb disorders were invited to return for an assessment of pain tolerance. A standardised algorithm was used to classify the 94 participants according to whether they had specific upper limb disorders (n = 22), non-specific arm pain (n = 15), or no arm pain (n = 57). Pain tolerance was assessed at three anatomical sites in each arm in response to electrocutaneous stimulation with alternating currents up to a maximum of 10 mA at three frequencies (5, 250, and 2000 Hz). A proportional odds model was used to compare pain tolerance thresholds according to sex, age, and diagnosis. Results: Women were less tolerant of pain than men (OR 0.13) and tolerance also declined with age (OR for one year increase in age 0.97). After allowance for sex and age, there was no indication that pain tolerance was lower in subjects with non-specific arm pain than in those with specific upper limb disorders or those who had no arm pain. Conclusions: The study hypothesis was not supported. However, before the hypothesis is dismissed, it should be tested further in patients with more severe and disabling arm pain.